Um teto todo seu na experiência literária de Conceição Evaristo - (:unkn) unknown (Universidade Federal do Pampa, 2021)
The present study has the purpose of intertwining the characterization of space given by Virginia Woolf in the work A Room of One's Own (1929), with the literary experience of Conceição Evaristo. With that, we have the title: A Room of One's Own in the literary experience of Conceição Evaristo. The general objective of this course conclusion work is to propose reflections on the possibility of recognizing the space category in Conceição Evaristo's writing activity. And the specific objectives are: to return to Virginia Woolf's heritage to think about the recognition of the space category and reflect on the writing space in Conceição Evaristo's proposal, recognizing the conceptual inheritance of her registries (“escrevivências”). The methodology consists of the previous readings of the works chosen for study, A Room of One's Own, by Virginia Woolf, and Becos da Memória, by Conceição Evaristo, as well as, it is based on qualitative research of bibliographic review on the relevance of the writing space, through other essays by Virginia Woolf, interviews given by the writer Conceição Evaristo and articles that deal with the theme of space. I consider that in Conceição Evaristo's literature, the physical space leaves traces that are identified through the clerk (“escrevivência”), which, in this sense, can be presented as a place that encompasses ancestry, memories, beliefs, and customs. Dare to research and bring together the writings of two authors from different eras, geography, and origins, it seems to be important to build a reflection to open narrow borders and that was not always evident in the literature. Keywords: A Room of One's Own. Writing space. Conceição Evaristo. Escrevivência.
Keywords: Evaristo, Conceição, 1946-; Woolf, Virginia, 1882-1941; Literatura brasileira; Escrita; Espaço e tempo na literatura; Escrevivência; Writing; Space and time in literature; Brazilian literature; CNPQ::LINGUISTICA, LETRAS E ARTES